Stosując wzór skróconego mnożenia, wykonaj działania:
a) (2x-1)(2x+1)
b) (⅕+a)(⅕-a)
c) (4/3x+1)(4/3x-1)
d) (x+√3)(x-√3)
e) (√2+y)(√2-y)
f) (√2/2 x+1)(√2/2 x-1)
g) (1/√3-2x)(1/√3+2x)
h) (5√5-x)(5√5+x)
i) (1⅕-x)(1⅕+x)

2

Odpowiedzi

2010-01-18T21:39:14+01:00
A) (2x-1)(2x+1) = 4x²-1
b) (⅕+a)(⅕-a) = 1/9-a²
c) (4/3x+1)(4/3x-1) = 48x²-1
d) (x+√3)(x-√3) = x²-3
e) (√2+y)(√2-y) = 2-y²
f) (√2/2 x+1)(√2/2 x-1) = ½x²-1
g) (1/√3-2x)(1/√3+2x) = ⅓-4x²
h) (5√5-x)(5√5+x) = 125-x²
i) (1⅕-x)(1⅕+x) = 16/9-x²
2010-01-18T21:55:04+01:00
A) (2x-1)(2x+1) = 4x² - 1
b) (⅕+a)(⅕-a) = 1/25 - a²
c) (4/3x+1)(4/3x-1) = 16/9x² - 1
d) (x+√3)(x-√3) = x² - 3
e) (√2+y)(√2-y) = 2 - y²
f) (√2/2 x+1)(√2/2 x-1) = 1/2 x² - 1
g) (1/√3-2x)(1/√3+2x) = 1/3 - 4x²
h) (5√5-x)(5√5+x) = 125 - x²
i) (1⅕-x)(1⅕+x) = 36/25 - x²